Identification and molecular characterization of Orf virus in Argentina - Peralta, Andrea Veronica (2015)
Orf virus (ORFV) is the etiological agent of contagious ecthyma (CE), a pustular dermatitis of sheep and goats. Outbreaks of ORFV have been observed in all geographical regions of the world, including Argentina. The origin and identity of Argentinian ORFVs are unknown, and no comparative or phylogenetic studies of these viruses have been performed. In this study, we described the sequencing and analysis of five ORFV molecular markers: a partial B2L gene (ORF011), VIR (ORF020), an envelope mature protein (ORF109), vIL10 (ORF127), and GIF (ORF117) from two particular Argentinian outbreaks of CE.